2016
DOI: 10.1177/8755122516653611
|View full text |Cite
|
Sign up to set email alerts
|

Drug Information Resources Used by Chain Community Pharmacists in Tennessee

Abstract: Background: Community pharmacists are a highly utilized drug information resource for patients and health care providers. Good retrieval skills and the availability of credible references are key to providing necessary information. Objective: This study aimed to identify the types of drug information resources used by chain community pharmacists in Tennessee. Methods: A phone survey was conducted by a trained pharmacy student to 39 pharmacists working at chain community pharmacies. Demographic questions, types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…We excluded retail chain pharmacies (companies with 4 locations: Walgreens, CVS, Raley's Pharmacy, Walmart, Costco, Rite-Aid, Safeway, Lucky's), given that previous research suggests that chain locations are likely to delay implementation at individual locations in favor of a system-wide protocol. [30][31][32] We also excluded medical system pharmacies, as well as those where the nature of the pharmacy or patient population excluded provision of PrEP and PEP: veterinary pharmacies, infusion center pharmacies, pediatric pharmacies, long-term care pharmacies, nuclear pharmacies, and compounding-only pharmacies. Four of the authors (N.N., J.P., R.B., S.M.)…”
Section: Samplementioning
confidence: 99%
“…We excluded retail chain pharmacies (companies with 4 locations: Walgreens, CVS, Raley's Pharmacy, Walmart, Costco, Rite-Aid, Safeway, Lucky's), given that previous research suggests that chain locations are likely to delay implementation at individual locations in favor of a system-wide protocol. [30][31][32] We also excluded medical system pharmacies, as well as those where the nature of the pharmacy or patient population excluded provision of PrEP and PEP: veterinary pharmacies, infusion center pharmacies, pediatric pharmacies, long-term care pharmacies, nuclear pharmacies, and compounding-only pharmacies. Four of the authors (N.N., J.P., R.B., S.M.)…”
Section: Samplementioning
confidence: 99%
“…Given the importance and the availability of diverse drug information (DI) sources ( Wong et al, 2009 ), several studies have been conducted in the United States (US) ( Poirier and Ascione, 1980 , Rae et al, 1992 , Gettig, 2008 , Moorman et al, 2017 ) and various other countries ( Zehnder et al, 2004 , Ball and Al-Othman, 2007 , Udezi et al, 2007 , MbchB et al, 2008 , Wong et al, 2009 , Khan and Shafie 2010, Chitme et al, 2014 , Borja-Hart and Leachman, 2016 , Asmelashe et al, 2017 ) to identify the DI sources that were most commonly used by pharmacists. However, little information is known about the types of drug information sources commonly used by pharmacists in Jordan (Wazaify et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Internet has made information more readily available to health care practitioners and their patients, but with this ease of access, users experience difficulties in identifying and filtering "the most useful, accurate, and credible sources while searching online for health information" [5]. For example, a 2015 survey found that 94% of community pharmacists in Tennessee used only electronic resources, including apps such as Epocrates and Lexicomp [6]. The results of that survey indicated that pharmacists were able to identify the gap in their resource use (most often related to primary resource availability), and the authors suggested that training could help pharmacists engage with drug information resources [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2015 survey found that 94% of community pharmacists in Tennessee used only electronic resources, including apps such as Epocrates and Lexicomp [6]. The results of that survey indicated that pharmacists were able to identify the gap in their resource use (most often related to primary resource availability), and the authors suggested that training could help pharmacists engage with drug information resources [6]. In other examples, surveys of medical residents and nurses showed that searches for information most frequently involved Google and Wikipedia, in addition to UpToDate and PubMed [7,8].…”
Section: Introductionmentioning
confidence: 99%